<em>The</em><em> </em><em>right</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>3</em><em>2</em><em>/</em><em>3</em><em>1</em>
<em>pl</em><em>ease</em><em> </em><em>see</em><em> the</em><em> attached</em><em> picture</em><em> for</em><em> full</em><em> solution</em>
<em>Hope </em><em>it</em><em> helps</em>
<em>Good</em><em> </em><em>luck</em><em> on</em><em> your</em><em> assignment</em>
Answer:
x = 1+√3 i/2 and x = 1-√3 i/2
Step-by-step explanation:
Given the expression x^2 - x+ 1, we are to factorize the expression as shown;
x^2 - x+ 1,
using the general formula
x = -(-1)±√1²-4(1)/2(1)
x = 1±√1-4/2
x= 1±√-3/2
x = 1±√3 i/2
Hence the required value of x are x = 1+√3 i/2 and x = 1-√3 i/2
122.1 or 122
becuase the original answer is 122.13 and the 3 gets out becuase it rounds down and so does the 1
Answer:
x = - 6
Step-by-step explanation:
Given
4(x + 6) - 2x = 12 ← distribute and simplify left side
4x + 24 - 2x = 12
2x + 24 = 12 ( subtract 24 from both sides )
2x = - 12 ( divide both sides by 2 )
x = - 6
Answer:
x = 9
Step-by-step explanation:
ur welcome